2005
DOI: 10.1097/01.coc.0000144852.75613.56
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and Gemcitabine in Malignant Pleural Mesothelioma: A Phase II Study

Abstract: Aims of this study were to evaluate the activity and toxicity of gemcitabine and cisplatin combination in malignant pleural mesothelioma (MPM). Patients with histologically proven MPM, < 75 years of age, Eastern Cooperative Oncology Group (ECOG) performance status (PS) < or = 2, and measurable MPM were eligible. Patients received gemcitabine 1250 mg/m intravenously on days 1 and 8 and cisplatin 75 mg/m on day 2, every 21 days, for a maximum of 6 cycles. From May 1999 to May 2001, 35 chemonaive patients (median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 18 publications
2
24
0
1
Order By: Relevance
“…1 In a malignancy with three major pathologic subtypes (epithelial, sarcomatoid, and biphasic), four sites of disease origin (pleura, peritoneum, pericardium, and tunica vaginalis), and several other key prognostic factors that can substantially affect outcomes, 27,28 it should not be surprising that six small phase II trials evaluating the gemcitabine/cisplatin combination in MM produced widely discordant results. [5][6][7][8][9][10] Therefore, to discern the impact of the addition of a novel agent to this chemotherapy backbone, we designed what we believe is the first randomized phase II trial ever performed in patients with MM. It demonstrates that the addition of bevacizumab to gemcitabine/cisplatin does not improve PFS in this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In a malignancy with three major pathologic subtypes (epithelial, sarcomatoid, and biphasic), four sites of disease origin (pleura, peritoneum, pericardium, and tunica vaginalis), and several other key prognostic factors that can substantially affect outcomes, 27,28 it should not be surprising that six small phase II trials evaluating the gemcitabine/cisplatin combination in MM produced widely discordant results. [5][6][7][8][9][10] Therefore, to discern the impact of the addition of a novel agent to this chemotherapy backbone, we designed what we believe is the first randomized phase II trial ever performed in patients with MM. It demonstrates that the addition of bevacizumab to gemcitabine/cisplatin does not improve PFS in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…This study also confirms the data from prior investigators regarding the significant activity of the gemcitabine/cisplatin combination in patients with MM. [3][4][5][6][7][8][9][10] The addition of bevacizumab to chemotherapy improves outcomes in cancers of the breast, colon, lung, and kidney. [32][33][34][35] Given preclinical data that supported a key role for the VEGF pathway in MM biology [12][13][14] and the multiple phase II trials that suggested modest activity for other VEGF inhibitors in patients with MM, 11,[15][16][17][18][19][20] it was plausible to assume that adding bevacizumab to systemic chemotherapy in patients with MM would replicate the results observed in these other cancers.…”
mentioning
confidence: 99%
“…The combination of cisplatin plus gemcitabine was also evaluated in some phase II trials suggesting that it may be an alternative in patients not candidates to pemetrexed, despite heterogeneity between studies with response rates and survival ranging from 12-48% and 9.5-12 months, respectively (3,(27)(28)(29)(30)(31). Furthermore, the use of carboplatin with gemcitabine has been investigated showing good tolerance and a response rate of 26% (32).…”
Section: First-line Combination Ctmentioning
confidence: 99%
“…On the basis of results in the metastatic disease, the association of carboplatin or cisplatin plus gemcitabine was considered as an effective treatment (Byrne et al,1999;Nowak et al, 2002;Favaretto et al, 2003;Castagneto et al, 2005;Kalmadi et al, 2008).…”
Section: Chemotherapy Regimens In the Neoadjuvant Setting Of Malignanmentioning
confidence: 99%